2012
DOI: 10.1159/000342217
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s Encephalopathy as a Treatable Adult-Onset Cerebellar Ataxia Mimicking Spinocerebellar Degeneration

Abstract: Background: Hashimoto’s encephalopathy (HE) presents with a variety of neurologic and neuropsychiatric features. In this study, we investigated the clinical and immunological profiles of the cerebellar ataxic form of HE. Methods: The clinical features, treatments, laboratory features, brain imaging, and serum anti-NH2-terminal of α-enolase autoantibodies (anti-NAE Abs), a useful diagnostic marker for HE, were investigated in 13 patients who presented with sporadic adult-onset cerebellar ataxia and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…However, rCBF was not decreased in the left prefrontal areas or anterior cingulate in either patient. We previously reported that 50% of patients with cerebellar ataxia tended to show decreased rCBF on brain SPECT imaging [7]. Our results were consisted with this report.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, rCBF was not decreased in the left prefrontal areas or anterior cingulate in either patient. We previously reported that 50% of patients with cerebellar ataxia tended to show decreased rCBF on brain SPECT imaging [7]. Our results were consisted with this report.…”
Section: Discussionsupporting
confidence: 91%
“…All patients were treated with corticosteroid therapy following SPECT acquisition and were improved as a result of therapy. The evaluated patients included 3 of our own cases that we have previously reported (cases 2, 6 and 7) [6,7,21]. The clinical features and laboratory findings of the patients are summarized in table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may be misdiagnosed with degenerative ataxia, especially spinocerebellar ataxia, given an all negative extensive workup, as has occurred in some reported cases with clinical features mimicking spinocerebellar ataxia 16,17. Since this is a treatable entity, we propose the inclusion of investigations for SREAT as a first or second tier in patients presenting with subacute or even chronic progressive cerebellar ataxia, so that an opportunity for treatment and improvement is not missed.…”
Section: Discussionmentioning
confidence: 99%
“…[1216] Various symptoms are used to define clinical subtypes of HE, such as the Creutzfeldt–Jakob disease-like form and the cerebellar ataxic form. [2224] However, the diversity of symptoms and the high prevalence of antithyroid antibodies in healthy populations may make the diagnosis of HE difficult. We discovered anti-NAE antibodies, autoantibodies that specifically recognize only the NH 2 -terminal of α-enolase, in the serum of patients with HE by proteomic analyses and demonstrated a high prevalence and specificity of these antibodies in patients with HE.…”
Section: Discussionmentioning
confidence: 99%